An empirical applicatin of a random level shift model with time-varying probability and mean reversion to the volatility of Latin-America forex market returns - Gonzáles Tanaka, José Carlos (Pontificia Universidad Católica del Perú, 2017)
Following Xu and Perron (2014), this paper uses daily data for six Forex Latin American markets (Argentina, Brazil, Chile, Colombia, Mexico and Peru). Four models of the family of the Random Level Shift (RLS) model are estimated: a basic model where probabilities of level shift are driven by a Bernouilli variable but probability is constant; a model where varying probabilities are allowed and introduced via past extreme returns; a model with mean reversion mechanism; and a model incorporating last two features. Our results prove three striking features: rst, the four RLS models t well the data, with almost all the estimates highly signi cant; second, the long memory property disappears completely from the ACF, including the GARCH effects; and third, the forecasting performance is much better for the RLS models against an overall of four competitor models: GARCH, FIGARCH and two ARFIMA models.

Siguiendo el trabajo de Xu y Perron (2014), este documento utiliza datos diarios de volatilidades de retornos cambiarios para seis mercados de América Latina (Argentina, Brazil, Chile, Colombia, Mexico and Peru). Cuatro modelos del tipo Random Level Shifts (RLS) son estimados: un modelo básico donde las probabilidades de cambios de nivel son gobernadas por una variable del tipo Bernouilli pero dicha probabilidad es constante; un modelo donde las probabilidades son cambiantes en el tiempo y dependen de los retornos bursátiles extremos negativos del periodo anterior; un modelo con reversión a la media; y un modelo que incorpora los dos aspectos mencionados anteriormente. Los resultados sugieren tres importantes aspectos: el primero es que los cuatro modelos RLS ajustan bien los datos con prácticamente todos los estimados altamente significativos; segundo, la característica de larga memoria desaparece completamente de la ACF, incluyendo los efectos GARCH; y, tercero, la performance de los cuatro modelos en términos de predicción es buena contra diferentes modelos rivales como los modelos GARCH, FIGARCH, y dos modelos ARFIMA.
Keywords: Acciones (Bolsa)--Pronóstico; Acciones (Bolsa)--Modelos econométricos; Bolsa de valores--Medición; América Latina--Bolsa de valores; https://purl.org/pe-repo/ocde/ford#5.02.01